Longing to Belong: A Phenomenological Inquiry into Enduring Effects of Cross-Cultural Life-World Transitions - Sobulis, Helena Teresa (Curtin University, 2018)
This research explores the life-changing effects of diaspora that can result in a cross-cultural childhood. It merges a phenomenological, hermeneutic, ethno-biographical and auto-ethnographical approach to explore the affective aspect of the cross-cultural childhood phenomenon within an existential framework using narrative inquiry to examine the lived experiences of three individuals who migrated to Australia. Empathetic resonance is developed through music interwoven in the text. Longing emerges as a central theme that offers great potential for personal growth.